Elderly Activities To Keep Your Knee Healthy - Metta Christiana; Ahmad Muhaimin; Andi Nurcahyo (Sean Institute, 2023)
Knee pain is one of the most common complaints among the elderly. At this age, the main cause is osteoarthritis or arthritis. In the environment around us, sometimes we still often encounter elderly people who are still active and healthy, even physically fit, full of ideas and still productive and even more physically fit than younger people The purpose of this study was to determine how the activities of the elderly to maintain knee health. The benefit of this research is for people who before entering old age can imitate and do the same thing to maintain knee health in old age. This research is a qualitative research with a phenomenological approach. The time approach used in this research is any time. The research population is elderly people in 3 sub-districts in the city of Semarang. The research sample was taken purposively to obtain informants according to the purpose of this study, namely elderly people who can provide information about how their activities are so that their knee health remains good. The researcher used 5 elderly people who had healthy knees as the main informants, while the trangulation informants were an anatomy lecturer and a physiotherapist. Data analysis used descriptive analysis (content analysis). The results of this study are that elderly people who have curved feet have better posture, because they can maintain body balance when standing, walking, running and jumping by distributing body weight evenly throughout the legs, elderly people must move their body by walking every day. days regularly or as often as possible, elderly people who do not consume milk have healthy knees, elderly people who do not take supplements for bones and joints still have healthy knees, elderly people should avoid movements that can cause knee arthritis . Advice that can be given is for elderly people who have flat feet should use footwear or shoes that are in accordance with the shape of the foot and the activity being carried out, consult a doctor about forms of exercise or exercise that are in accordance with health conditions, maintain normal weight, avoid activities or sports that put excessive stress on the legs, take time for a quick warm-up before moving, cooling is as important as warming up, moving the body by walking or any movement for at least 20-30 minutes per day on a regular basis or at any time, exercising all muscles support the knee. (Can walk, bike or swim).